Parkinson’s disease, epilepsy, and amyotrophic lateral sclerosis—emerging role of AMPA and kainate subtypes of ionotropic glutamate receptors - Vukolova, Marina N.; Yen, Laura Y.; Khmyz, Margarita I.; Sobolevsky, Alexander I.; Yelshanskaya, Maria V. (Frontiers in Cell and Developmental Biology, 2023)
Ionotropic glutamate receptors (iGluRs) mediate the majority of excitatory neurotransmission and are implicated in various neurological disorders. In this review we discuss the role of the two fastest iGluRs subtypes, AMPA and kainate receptors, in the pathogenesis and treatment of Parkinson's disease, epilepsy and amyotrophic lateral sclerosis. While both AMPA and kainate receptors represent promising therapeutic targets for the treatment of these diseases, many of their antagonists show adverse side effects. Further studies of factors affecting selective subunit expression and trafficking of AMPA and kainate receptors as well as reasonable approach to their regulation by recently identified novel compounds remain promising directions for pharmacological research.